Conceptual Approaches to the Study of Nature of Private Ownership of Private Subsidiary Farming during Post-Socialist Transformation in Agricultural Sector - SHINET, Gulzada; MYRZALIYEV, Borash; YDYRYS, Serikbay (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The article discusses the ownership rights theory, which is one of the most striking examples of the so-called ‘economic imperialism’, where the essence of private subsidiary farming (households) comes from, which is a type of activity to meet one’s own needs on land plots located in rural areas of Kazakhstan. The purpose of the work is to study market transformation in agriculture of post-socialist countries to improve attitudes to personal ownership in the sphere of social production and its social orientation. The basis of mechanism for the implementation of the desired goals is the process of transformation of system of ownership relations through the introduction of personal ownership of the means of production as a necessary and sufficient condition to create a liability mechanism for economically efficient use of production resources, strengthening of the motives for labor efficiency and entrepreneurship in agriculture.